Removal of cadmium from aqueous solutions using excised leaves of Quetta pine (Pinus halepensis Mill.) - Rahman, M; Gul, S; Ajmal, M; Iqbal, A; Achakzai, Akk (Bangladesh Journal of Botany, 2015)
Removal of cadmium from aqueous solution was studied by using Quetta pine (Pinus halepensis Mill.) leaves. Batch adsorption experiments were performed as a function of appropriate equilibrium time, pH, concentration of adsorbate and amount of adsorbent. The optimum pH required for maximum adsorption was found to be 7.0 and the maximum contact time for the equilibrium was 30 minutes at adsorbent dose of 10 g. The maximum adsorption efficiency of cadmium removal was 98.50%. The results were better fitted by Langmuir than Freundlich isotherm. The separation factor of equilibrium 0.12 and 0.67 showed that Quetta pine leaves are good adsorbent of cadmium from aqueous solution DOI: http://dx.doi.org/10.3329/bjb.v43i3.21598 Bangladesh J. Bot. 43(3): 277-281, 2014 (December)